Strengthening elementary school teachers’ competence in the development and implementation of Deep Learning-based instructional materials - Jumanto Jumanto; Anggit Grahito Wicaksono; Elinda Rizkasari (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2026)
This community service program aimed to strengthen elementary school teachers’ competence in developing and implementing Deep Learning-based instructional materials within the Kurikulum Merdeka framework. The program was conducted at SD Negeri Sidorejo 03, Sukoharjo, involving 35 teachers through workshops, guided practice, mentoring, and evaluation activities. The training focused on helping teachers design contextual and reflective teaching modules that support meaningful learning processes. The results showed improvements in teachers’ understanding and practical skills in preparing deep learning-based instructional materials, reflected in the increase of average scores from 74.13 in the pretest to 91.73 in the posttest. In addition, teachers demonstrated better readiness to apply deep learning principles in classroom instruction and successfully developed teaching modules relevant to students’ learning contexts. Participants also responded positively to the program and considered the training useful in supporting instructional innovation. This program contributed to strengthening teachers’ pedagogical competence and provided a foundation for the sustainable implementation of deep learning practices in elementary schools.